Mechanical thrombectomy for symptomatic stent thrombosis after carotid artery stenting - You-Min Fan; Han-Yang Liu; Yu-Yang Xue (Frontiers in Neurology, 2023)
BackgroundAs there is still no consensus on the treatment of carotid stent thrombosis (CST), we would like to describe our experience with the revascularization of CST by mechanical thrombectomy.MethodsWe retrospectively studied patients who underwent mechanical thrombectomy after CST at Xuzhou Municipal First People’s Hospital and Xuzhou Central Hospital between January 2020 and November 2022. The results of the procedures, complications, and clinical and imaging follow-up were recorded.ResultsA total of six patients were included in this study. The stenosis grade before stent implantation was ≥85% in all patients, and the stenosis length ranged from 7 to 20 mm. Patients experienced CST within 6 days to 45 months after carotid artery stenting (CAS); the median admission on the National Institutes of Health Stroke Scale (NIHSS) at CST was 12 (range 8–25). Mechanical thrombectomy was successfully performed in all patients. There was no periprocedural death, and the modified Rankin Scale (mRS) at the 3-month follow-up was 0–2. All patients showed recovery from their neurological deficits.ConclusionThe treatment of symptomatic CST with mechanical thrombectomy resulted in satisfactory clinical outcomes. This regimen could be effective and safe, and future prospective and randomized studies are warranted.